Neuropeptide Y regulates the hematopoietic stem cell microenvironment and prevents nerve injury in the bone marrow. (27th April 2015) - Park, Min Hee; Jin, Hee Kyung; Min, Woo‐Kie; Lee, Won Woo; Lee, Jeong Eun; Akiyama, Haruhiko; Herzog, Herbert; Enikolopov, Grigori N; Schuchman, Edward H; Bae, Jae‐sung
Abstract Many reports have revealed the importance of the sympathetic nervous system (SNS) in the control of the bone marrow environment. However, the specific role of neuropeptide Y (NPY) in this process has not been systematically studied. Here we show that NPY‐deficient mice have significantly reduced hematopoietic stem cell (HSC) numbers and impaired regeneration in bone marrow due to apoptotic destruction of SNS fibers and/or endothelial cells. Furthermore, pharmacological elevation of NPY prevented bone marrow impairments in a mouse model of chemotherapy‐induced SNS injury, while NPY injection into conditional knockout mice lacking the Y1 receptor in macrophages did not relieve bone marrow dysfunction. These results indicate that NPY promotes neuroprotection and restores bone marrow dysfunction from chemotherapy‐induced SNS injury through the Y1 receptor in macrophages. They also reveal a new role of NPY as a regulator of the bone marrow microenvironment and highlight the potential therapeutic value of this neuropeptide.